2022
DOI: 10.1038/s41598-022-17583-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and mitigating clinical samples matrix effects on TX-TL cell-free performance

Abstract: Cell-free biosensors are promising tools for medical diagnostics, yet their performance can be affected by matrix effects arising from the sample itself or from external components. Here we systematically evaluate the performance and robustness of cell-free systems in serum, plasma, urine, and saliva using two reporter systems, sfGFP and luciferase. In all cases, clinical samples have a strong inhibitory effect. Of the different inhibitors, only RNase inhibitor mitigated matrix effects. However, we found that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Others have recently assessed those impacts and begun to address them in similar systems. [30,31] In contrast, the described assay is a viable alternative, as the 5100 nt RNA fragment was more efficient in triggering detection in the TEVp amplification system and the LOD was less than 15,000 copies with an ere DNA in a magnetic tweezers assay correlates with the length of the strand used for invasion. [32] Future work is needed to determine which factors such as location of the trigger sequence within the large RNA (5′ end which is our case, internal or 3′ end), whether secondary structure associated with the invading RNA strand is a factor (the SARS-Covid RNA has extensive secondary structure) and if there is a relationship between trigger RNA size and efficiency of toehold switch activation.…”
Section: Discussionmentioning
confidence: 99%
“…Others have recently assessed those impacts and begun to address them in similar systems. [30,31] In contrast, the described assay is a viable alternative, as the 5100 nt RNA fragment was more efficient in triggering detection in the TEVp amplification system and the LOD was less than 15,000 copies with an ere DNA in a magnetic tweezers assay correlates with the length of the strand used for invasion. [32] Future work is needed to determine which factors such as location of the trigger sequence within the large RNA (5′ end which is our case, internal or 3′ end), whether secondary structure associated with the invading RNA strand is a factor (the SARS-Covid RNA has extensive secondary structure) and if there is a relationship between trigger RNA size and efficiency of toehold switch activation.…”
Section: Discussionmentioning
confidence: 99%
“…While the addition of a commercially available RNase inhibitor is a quick and simple strategy to improve CFE function in the presence of complex samples, this approach increases the cost of each reaction and can reduce reaction efficiency in terms of total protein expression, as we observed with the BreR CFE sensor. To address these drawbacks, other studies have prepared CFE extract from E. coli cells overexpressing RNase inhibitors, which maintained the function of CFE reactions in the presence of saliva, blood, serum, and urine without the need for an additional reagent. While the addition of RNase inhibitor successfully restored the function of the BreR CFE sensor in the presence of wastewater and blood serum, it did not improve function in the presence of 2.5 mg/mL fecal water. We speculate that this effect could be due to the presence of proteases in feces, which are particularly abundant in the human gut .…”
Section: Discussionmentioning
confidence: 99%
“…Expanding the functional and application repertoire of bioprinted ELM-based sensing devices is expected to bring significant advantages to the biosensor field, such as the realization of easy to use multi-functional materials for different applications, obtained via highly reproducible and parallelized biofabrication techniques. ELM devices are also expected to provide advantages over cell-free expression-based sensing methods, which include promising portable testing devices but are more sensitive to matrix effects, e.g., inhibitors, than whole-cell sensing systems, although recent efforts demonstrated that a mitigation of such effects could be achieved [ 35 ].…”
Section: Introductionmentioning
confidence: 99%